Effectiveness of Feed Feeding Containing Fermented Papaya Leaves (Carica papaya L.) Solutions on The Appearance of Erythrocyte and The Growth of Jambal Siam Fish (Pangasianodon hypophthalmus) - Latifah Hannum Lase; Iesje Lukistyowati; Henni Syawal (Jurusan Budidaya Perairan, Fakultas Perikanan dan Kelautan, Universitas Riau, 2022)
Papaya leaves (Carica papaya L.) contain compounds such as tannins, flavonoids, tocophenols, carpain alkaloids, and papain enzymes which have proteolytic activity, antimicrobial and can be used as an immunomodulators that can strengthen the immune system. The purpose of this study was to obtain the best dose of adding fermented papaya leaf solution to feed to improve the health of jambal siam fish (P. hypophthalmus). The method used is an experimental method using a one-factor Completely Randomized Design (CRD) with five treatment levels and three replications. The treatments used were Kn (Negative Control): The feed was not added with fermented papaya leaf solution and was not tested against Aeromonas hydrophila, Kp (Positive Control): The feed was not added with fermented papaya leaf solution but was tested against A. hydrophila), and feed added with fermented papaya leaf solution at a dose of P1 (16 ml/kg), P2 (18 ml/kg), P3 (20 ml/kg) and challenged with A. hydrophila bacteria. The fish were kept for 46 days. The challenge test of A. hydrophila was carried out on the 32nd day intramuscularly with a density of 108 CFU/ml with a dose of 0.1 ml/head. The results showed that the best dose of fermented papaya leaves added to the feed was found in P3 (20 ml/kg) treatment with a total erythrocyte of 284,33 x 104 cells/mm3, the hematocrit value was 38.67%, and the hemoglobin level was 10.67 g/dL, with weight growth absolute 7.80 g. Water quality ranges from 27 – 30 oC, pH 5.5 – 7, DO 4.3 – 5.8 ppm, and ammonia 0.017 – 0.023 mg/L.